The Role of Semarang Healthy Market Activities in the Development of Healthy Food SME’s in Semarang City - Hannun, Delta Mutiara (Badan Riset dan Inovasi Daerah Provinsi Jawa Tengah, 2023)
One of the community role in national economic development is applied on Micro, Small, and Medium Enterprises (MSMEs). MSMEs has a dominant contribution in the Indonesian economy, because of the large number of industries in every economic sector; the great potency in employment creation, and the contribution of MSMEs in the formation of Gross Domestic Product. This study aims to analyze the activities of the Semarang Healthy Market (Pasar Sehat Semarang/PSS), the barriers to partner MSME management activities, and the role of the Semarang Healthy Market in the development of healthy food MSMEs in Semarang City. The method for determining respondents based on purposive sampling, which the total number of respondents is 47 administrators from 17 SMEs active partner in PSS. The data were analyzed using quantitative descriptive with statistical analysis tools in the form of Pearson correlation analysis. The results show that PSS is a kind of pop-up market with a healthy food theme in every Sunday and has the main activity on Healthy Market and Healthy Class. Barriers to the management of MSMEs partner at Pasar Sehat Semarang include capital, human resources, technology utilization, managerial and accountancy skills, branding, marketing, and accessibility. Based on a p-value of 0,013 on the correlation test, it means that there is a significant positive relationship between the Semarang Healthy Market and the development of MSMEs. The correlation number of 0,361 shows that the two variables have a low correlation and do not really influence each other.